The Role of Total Body Fluid in Pulmonary Tuberculosis Patients with Risk of Obstructive Sleep Apnea - Qinaya Wrahty Adeta; Edward Pandu Wiriansya; Marzelina Karim; Aryanti R Bamahry; Dwi Anggita (Ann Publisher, 2026)
Background: Pulmonary Tuberculosis (TB) patients are vulnerable to sleep-disordered breathing, particularly Obstructive Sleep Apnea (OSA), due to chronic pulmonary inflammation, structural lung damage, and systemic metabolic disturbances. Alteration of total body fluid, especially extracellular fluid accumulation, may contribute to upper airway collapsibility through rostral fluid shift during sleep. However, evidence regarding the relationship between total body fluid and OSA risk in TB patients remains limited. Aim: An analytic observational study with a cross-sectional design was conducted on 85 TB patients selected using total sampling. OSA risk was assessed using the STOP-BANG questionnaire and categorized as mild, moderate, and severe. Total body water was measured using Bioelectrical Impedance Analysis (BIA) and classified as low, normal, or high. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Results: The prevalence of OSA risk was high, with 34.1% mild, 32.9% moderate, and 32.9% severe. Most respondents had normal body fluid (68.2%), while 23.5% had high fluid levels. A significant association was found between OSA risk and total body fluid (p = 0.000). Patients with severe OSA showed a markedly higher proportion of fluid overload (46.6%) compared to those with mild OSA (10.3%). Conclusion: There is a significant relationship between OSA risk and total body fluid in TB patients. Higher OSA severity is associated with increased likelihood of fluid overload. Assessment of hydration status should be included in TB management to reduce the risk of respiratory complications and sleep disturbances. Keywords: Pulmonary Tuberculosis, obstructive sleep apnea, total body fluid, bioelectrical impedance analysis, STOP-BANG.